2011
DOI: 10.1126/science.1209840
|View full text |Cite
|
Sign up to set email alerts
|

The Large, Oxygen-Rich Halos of Star-Forming Galaxies Are a Major Reservoir of Galactic Metals

Abstract: The circumgalactic medium (CGM) is fed by galaxy outflows and accretion of intergalactic gas, but its mass, heavy element enrichment, and relation to galaxy properties are poorly constrained by observations. In a survey of the outskirts of 42 galaxies with the Cosmic Origins Spectrograph onboard the Hubble Space Telescope, we detected ubiquitous, large (150 kiloparsec) halos of ionized oxygen surrounding star-forming galaxies, but we find much less ionized oxygen around galaxies with little or no star formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

67
736
9

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(812 citation statements)
references
References 41 publications
67
736
9
Order By: Relevance
“…There is also a significant fraction of the blue galaxies showing large velocity differences between the radial velocity of the absorber and central galaxy (Dv up to 500 km s −1 ). Taken together with the COS-Halos results on the presence (absence) of highly ionized gas (seen as O VI absorbers Tumlinson et al 2011) in blue (red) galaxies, there are therefore real differences between the CGM surrounding star-forming and quiescent galaxies. Unfortunately, as discussed in Section 3.1, the data from the COS-GASS do not cover O VI; thus, we are not able to do the same analysis as done by Tumlinson et al (2011) for the combined sample.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…There is also a significant fraction of the blue galaxies showing large velocity differences between the radial velocity of the absorber and central galaxy (Dv up to 500 km s −1 ). Taken together with the COS-Halos results on the presence (absence) of highly ionized gas (seen as O VI absorbers Tumlinson et al 2011) in blue (red) galaxies, there are therefore real differences between the CGM surrounding star-forming and quiescent galaxies. Unfortunately, as discussed in Section 3.1, the data from the COS-GASS do not cover O VI; thus, we are not able to do the same analysis as done by Tumlinson et al (2011) for the combined sample.…”
Section: Discussionmentioning
confidence: 59%
“…Similar ionization parameters were also estimated by Shull et al (2009) 2 that are seen in our sample. Therefore, it is likely that most of these highly ionized absorbers are different from those detected in various other CGM and QSO-absorption studies (Chen et al 2001a;Wakker & Savage 2009;Tumlinson et al 2011;Borthakur et al 2013;Bordoloi et al 2014, and references therein). However, as discussed in detail by Werk et al (2014), Fox et al (2013), Meiring et al (2013), Lehner et al (2013), Tripp et al (2011), and references therein, O VI may represent a different phase of gas that differs from the ones traced by lower ionization transitions.…”
mentioning
confidence: 75%
“…Future work will analyze the source of metals, their eventual location, and the relative rates of pristine versus enriched accretion. Such metal distribution mechanisms can be directly constrained by observations of metal absorption lines in quasar spectra passing near galaxies, such as that obtained from the COS-Halos program (Tumlinson et al 2011;Ford et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In the case, if the starburst activity lasts long time ( 300 Myr) or there are repeated bursts at the centre, the outflow properties (viz. velocity, metallicity etc) at ∼ 100-200 kpc also can be connected to the ongoing star formation process, as observed by Tumlinson et al (2011). Suppose one had defined the outer mass loading factor as the ratio between averaged mass outflow rate and the SFR as…”
Section: Definition Of Mass Loading Factormentioning
confidence: 93%
“…The mass loading factor estimated at the virial radius has important implications for understanding dynamical processes accompanying enrichment of the Universe. Recent observations of the extended circum-galactic haloes bearing metals up to distances 100 -200 kpc from the parent galaxy (Tumlinson et al 2011;Bordoloi et al 2014;Mathes et al 2014) call for a long-term numerical study covering passage of the outflows through the virial threshold. Hopkins et al (2012) also found that the outflowing gas is mostly dominated by warm gas (10 4 < T < 4 × 10 5 K), which is consistent with the results of Melioli et al (2013) who have simulated the outflow from M82.…”
Section: Introductionmentioning
confidence: 99%